Empirical Study on the Determinants of Stock Returns: Evidence from the Banking Industry in Indonesia - Puspita, Aida Indah; Ratnawati, Dyah (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2025)
Stock returns are a crucial element in investment, indicating the anticipated rate of return for investors. Thus, it is essential for investors to comprehend the elements that may affect stock returns. This study seeks to ascertain the impact of profitability, dividend policy, and company size on stock returns. This research is a quantitative analysis of secondary data obtained from the financial statements of banking firms listed on the IDX for the years 2019-2023. The sampling method employed was purposive sampling, which produced 12 corporate samples over a 5-year duration, resulting in a total of 60 data units. The analytical method employed was multiple linear regression analysis. The research findings indicate that profitability represented by ROE, has a significantly favorable impact on stock returns, signifying the company's capacity to make profits as an affirmative signal for investors. The dividend policy represented by the Dividend Payout Ratio (DPR), exerts a substantial negative influence, suggesting that investors choose firms that reinvest earnings for prospective growth. The company's size indicated by Ln total assets, does not influence stock returns due to a shift in investor attention from 2019 to 2023 towards smaller more adaptable banks, in contrast to larger less creative banks.